Extracellular polysaccharide-facilitated selenium nanoparticle assembly and metabolic reprogramming support efficient selenite biotransformation by ARTP-mutagenized Lactiplantibacillus plantarum Vse252 - Lihui Tan; Xinyan Wang; Lin Hu; Xiang Gen; Shirui Yu; Xue Li; Xinyu Yan; Bo He; Jun Zhang; Yongzhong Wang; Hengqian Lu (Bioresource Technology, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Cellulose nanocrystal-based antimicrobial porous foam loaded with cinnamaldehyde for enhanced chilled meat preservation - Jin-ling Wu; Ai-ling Zhong; Rui Zhang; Hai-yan Huang; Teng-gen Hu; Zhen-lin Xu; Hong Wang; Peng Wen (Food Packaging and Shelf Life, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Research on Fracture Characteristics and Crack Propagation Patterns of Freeze-Thaw Damaged Rock Under Loading - Ding Ma; Mei-lu Yu; Lin-kai He; Zhong-wen Wang; Zi-yi Yang; Gen-shui Wu (Applied Geophysics, 2026)

Tartary buckwheat-soy protein isolate composite gels: gelling, rheological, water-retention, and texture characteristics at different ratios - Xiao Han; Gen Ma; Lin Wang; Ting Cheng; Yangyang Guo; Liangzhen Jiang; Yan Wan; Xiaoqin Zheng; Changying Liu; Lianxin Peng; Gang Zhao; Xiulan Guo; et al. (Food Hydrocolloids, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Natural-product-derived carbon dots to combat Candida albicans infections without drug resistance by multifaceted antifungal mechanisms - Babar Khan; Haiyan Wang; Yun Wang; Faisal Latif; Peiya Chen; Mengyuan Han; Kejia Feng; Yonghao Ye; Fu-Gen Wu; Fengming Lin (Chemical Engineering Journal, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Devosia lacusdianchii sp. nov., an attached bacterium inhibited by metabolites from its symbiotic Microcystis - Qing-Lin Deng; Yao Xiao; Ru Jia; Xin Xie; Le Wang; Xin Wang; Jian-Yuan Yang; Qi-Gen Guo; Bing-Huo Zhang (Antonie van Leeuwenhoek, 2024)

Synergistic structure engineering and electrochemical activation modulating vanadium oxide cathode toward superior zinc-ion storage - Kan Fang; Heng Zhang; Peng Chen; Hua-Yu Zhang; Zhan Wei; Ling Ding; Xiao-Ai Ye; Jiawang Liu; Yi-Lin Liu; Gui-Gen Wang; Hui Ying Yang (Chemical Engineering Journal, 2024)

Corrigendum to ““One stone, five birds”: Ultrabright and multifaceted carbon dots for precise cell imaging and glutathione detection” [Chem. Eng. J. 457 (2023) 140997] - Zihao Wang; Ke-Fei Xu; Gang Wang; Samran Durrani; Fengming Lin; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Preparing a heavy-metal adsorbent based on alginate-like extracellular polymers from conventional activated sludge via polyethyleneimine grafting - Chen Shi; Run-Gen Zeng; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Xiao-Di Hao; Nan Zhang; Yuan-Yuan Wu (Sustainable Chemistry and Pharmacy, 2024)

Multifunctional phosphorus-containing imidazoliums endowing one-component epoxy resins with superior thermal latency, heat resistance, mechanical properties, and fire safety - Jingsheng Wang; Jun Wang; Shuang Yang; Xi Chen; Kaiwen Chen; Gen Zhou; Xian Liu; Lin Xu; Siqi Huo; Pingan Song; Hao Wang (Chemical Engineering Journal, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Continuous extensional uplift controls the Silurian structural evolution of the Sichuan Basin, southwest China - Gen Li; Zhong-Quan Li; Dian Li; Heng-Lin Liu; Shan Yan; Gui-Ping Su; Xing-Wang Tian (Marine and Petroleum Geology, 2023)

New evidence of the Hoyle-like structure in 16O - Jiahao Chen; Yanlin Ye; Kai Ma; Jiaxing Han; Dongxi Wang; Chengjian Lin; Huiming Jia; Lei Yang; Gen Li; Lisheng Yang; Ziyao Hu; Zhiwei Tan; et al. (Science Bulletin, 2023)

Durable dual-methylpiperidinium crosslinked poly(binaphthyl-co-terphenyl piperidinium) anion exchange membranes with high ion transport and electrochemical performance - Wei Ting Gao; Xue Lang Gao; Yvonne Shuen Lann Choo; Jia Jun Wang; Zhi Hong Cai; Qiu Gen Zhang; Ai Mei Zhu; Qing Lin Liu (Chemical Engineering Journal, 2023)

“One stone, five birds”: Ultrabright and multifaceted carbon dots for precise cell imaging and glutathione detection - Zihao Wang; Ke-Fei Xu; Gang Wang; Samran Durrani; Fengming Lin; Fu-Gen Wu (Chemical Engineering Journal, 2023)

Algogenic organic matter derived DBPs: Precursor characterization, formation, and future perspectives – A review - Lap-Cuong Hua; Chun-Hsi Lai; Gen-Shuh Wang; Tsair-Fuh Lin; Chihpin Huang (Critical Reviews in Environmental Science and Technology, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Mapping QTL for Omega-3 Content in Hybrid Saline Tilapia - Grace Lin; Le Wang; Si Te Ngoh; Lianghui Ji; Laszlo Orbán; Gen Hua Yue (Marine Biotechnology, 2018)

Effect of climate change on seasonal water use efficiency in subalpine Abies fabri - Xiang-yang Sun; Gen-xu Wang; Mei Huang; Zhao-yong Hu; Chun-lin Song (Journal of Mountain Science, 2017)

The genus Fusariella - Chuan-Gen Lin; Yun Chen; Eric H. C. McKenzie; Darbhe J. Bhat; Hiran A. Ariyawansa; Kevin D. Hyde; Yong Wang (Mycological Progress, 2016)

A genome-wide analysis of the ASYMMETRIC LEAVES2/LATERAL ORGAN BOUNDARIES (AS2/LOB) gene family in barley (Hordeum vulgare L.) - Bao-jian Guo; Jun Wang; Shen Lin; Zheng Tian; Kai Zhou; Hai-ye Luan; Chao Lyu; Xin-zhong Zhang; Ru-gen Xu (Journal of Zhejiang University-SCIENCE B, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

The Effect on Sodium/Iodide Symporter and Pendrin in Thyroid Colloid Retention Developed by Excess Iodide Intake - Xiao-yi Chen; Chu-hui Lin; Li-hua Yang; Wang-gen Li; Jin-wei Zhang; Wen-wei Zheng; Xiang Wang; Jiang Qian; Jia-luan Huang; Yi-xiong Lei (Biological Trace Element Research, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Heat stress impairs mice granulosa cell function by diminishing steroids production and inducing apoptosis - Man Luo; Lian Li; Cheng Xiao; Yu Sun; Gen-Lin Wang (Molecular and Cellular Biochemistry, 2016)

Synchronized dynamics of bacterial niche‐specific functions during biofilm development in a cold seep brine pool - Weipeng Zhang; Yong Wang; Salim Bougouffa; Renmao Tian; Huiluo Cao; Yongxin Li; Lin Cai; Yue Him Wong; Gen Zhang; Guowei Zhou; Xixiang Zhang; Vladimir B. Bajic; et al. (Environmental Microbiology, 2015)
Summary The biology of biofilm in deep‐sea environments is barely being explored. Here, biofilms were developed at the brine pool (characterized by limited carbon sources) and the normal bottom water adjacent to T huwal cold seeps. Comparative metagenomics based on 50 Gb datasets identified polysaccharide degradation, nitrate reduction and proteolysis as enriched functional categories for brine biofilms. The genomes of two dominant species: a novel D eltaproteobacterium and a novel E psilonproteobacterium in the brine biofilms were reconstructed. Despite rather small genome sizes, the D eltaproteobacterium possessed enhanced polysaccharide fermentation pathways, whereas the E psilonproteobacterium was a versatile nitrogen reactor possessing nar , nap and nif gene clusters. These metabolic functions, together with specific regulatory and hypersaline‐tolerant genes, made the two bacteria unique compared with their close relatives, including those from hydrothermal vents. Moreover, these functions were regulated by biofilm development, as both the abundance and the expression level of key functional genes were higher in later stage biofilms, and co‐occurrences between the two dominant bacteria were demonstrated. Collectively, unique mechanisms were revealed: (i) polysaccharides fermentation, proteolysis interacted with nitrogen cycling to form a complex chain for energy generation, and (ii) remarkably exploiting and organizing niche‐specific functions would be an important strategy for biofilm‐dependent adaptation to the extreme conditions.

Patients with type 2 diabetes exhibit cognitive impairment with changes of metabolite concentration in the left hippocampus - Yue Wang; Xiao-yun Xu; Chun-hua Feng; Yuan-ling Li; Xia Ge; Gen-lin Zong; Yi-bin Wang; Bo Feng; Peng Zhang (Metabolic Brain Disease, 2015)

XRCC1 Arg399Gln and clinical outcome of platinum-based treatment for advanced non-small cell lung cancer: a meta-analysis in 17 studies - Jian Chen; Qing-wei Zhao; Gen-ming Shi; Lin-run Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Cloning, expression and characterization of meso-2,3-butanediol dehydrogenase from Klebsiella pneumoniae - Gen Lin Zhang; Cui Wei Wang; Chun Li (Biotechnology Letters, 2012)

Effect of pH on the Analysis of 2-MIB and Geosmin in Water - Wen-Hsing Hsieh; Wei-Nung Hung; Gen-Shuh Wang; Shu-Ting Hsieh; Tsair-Fuh Lin (Water, Air, & Soil Pollution, 2012)

Effects of temperature change on water discharge, and sediment and nutrient loading in the lower Pearl River basin based on SWAT modelling - Ying Li; Bao-Ming Chen; Zhong-Gen Wang; Shao-Lin Peng (Hydrological Sciences Journal, 2011)

Role of desert annuals in nutrient flow in arid area of Northwestern China: a nutrient reservoir and provider - Bao-Ming Chen; Gen-Xuan Wang; Shao-Lin Peng (Plant Ecology, 2009)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Impact of genetic polymorphisms of leptin and TNF-α on rosiglitazone response in Chinese patients with type 2 diabetes - Hai-Ling Liu; Yang-Gen Lin; Jing Wu; Hong Sun; Zhi-Cheng Gong; Ping-Cheng Hu; Ji-Ye Yin; Wei Zhang; Dan Wang; Hong-Hao Zhou; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2008)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Spatial-temporal variation of heavy metal elements content in covering soil of reclamation area in fushun coal mine - Jun-bao Yu; Jing-shuang Liu; Jin-da Wang; Zhong-gen Li; Xue-lin Zhang (Chinese Geographical Science, 2002)

The Arterial Supply of the Carpal Joint in the Bactrian Camel (Camelus Bactrianus) - Jian-Lin Wang; Cui-Sheng; Gen-Xuan Wang; Hai-Yan Li (Veterinary Research Communications, 2000)

The Arterial Supply of the Cubital Joint in the Bactrian Camel (Camelus bactrianus) - Jian-Lin Wang; Gao-Lan; Cui-Sheng; Gen-Xuan Wang; Hai-Yan Li (Veterinary Research Communications, 2000)